LAW ENFORCEMENT AGAINST MOTORCYCLE MURDER ACTIONS RESULTING IN LOSS OF LIVES IN THE LEGAL SYSTEM IN INDONESIA - Muhammad Daud Tarigan; Ismaidar, Ismaidar; Muhammad Arif Sahlepi (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study examines the phenomenon of vigilante action that often occurs in Indonesian society, especially in the context of Begal perpetrators who have resulted in loss of life. The main focus of this study is to understand the application of criminal law to perpetrators of vigilante action, by exploring the relevant legal provisions in the Criminal Code (KUHP) and their implications in resolving cases. This study is descriptive analytical and uses a normative legal method with a literature study approach, involving primary, secondary, and tertiary legal materials. The results of the study show that, although the Criminal Code does not explicitly regulate vigilantism, articles such as Article 170 on violence, Article 351 on assault, and Article 354 on serious assault, can be applied to prosecute perpetrators. The cases raised in this study show that vigilantism is often motivated by public disappointment with the police response which is considered slow and ineffective. This causes a strong reaction from the public which leads to persecution or even murder of perpetrators of crimes caught by the masses. The study recommends the need for more effective and responsive law enforcement by law enforcement officers and increased legal education for the community to reduce vigilante actions. Increasing public trust in law enforcement agencies is also very important to prevent the community from taking legal action into their own hands.